Synergistic Effect of Cobalt and Iron in Layered Double Hydroxide Catalysts for the Oxygen Evolution Reaction. Issue 1 (21st December 2016) - Yang, Fengkai; Sliozberg, Kirill; Sinev, Ilya; Antoni, Hendrik; Bähr, Alexander; Ollegott, Kevin; Xia, Wei; Masa, Justus; Grünert, Wolfgang; Cuenya, Beatriz Roldan; Schuhmann, Wolfgang; Muhler, Martin
Abstract: Co‐based layered double hydroxide (LDH) catalysts with Fe and Al contents in the range of 15 to 45 at % were synthesized by an efficient coprecipitation method. In these catalysts, Fe 3+ or Al 3+ ions play an essential role as trivalent species to stabilize the LDH structure. The obtained catalysts were characterized by a comprehensive combination of surface‐ and bulk‐sensitive techniques and were evaluated for the oxygen evolution reaction (OER) on rotating disk electrodes. The OER activity decreased upon increasing the Al content for the Co‐ and Al‐based LDH catalysts, whereas a synergistic effect in Co‐ and Fe‐based LDHs was observed, which resulted in an optimal Fe content of 35 at %. This catalyst was spray‐coated on Ni foam electrodes and showed very good stability in a flow‐through cell with a potential of approximately 1.53 V at 10 mA cm −2 in 1 m KOH for at least 48 h. Abstract : Iron‐ing out the kinks : Co‐based layered double hydroxide (LDH) catalysts are evaluated for the oxygen evolution reaction (OER), and the activity is found to decrease upon increasing the Al content for the Co‐ and Al‐based LDH catalysts, whereas a synergistic effect in Co‐ and Fe‐based LDHs is observed. The best CoFe LDH catalyst has very good stability on 1×1 cm 2 Ni foam electrode in a flow‐through cell with a potential of approximately 1.53 V at 10 mA cm −2 in 1 m KOH for at least 48 h.